The collected works of Dbal-maṅ Dkon-mchog-rgyal-mtshan - Dbal-maṅ Dkon-mchog-rgyal-mtshan, 1764-1853 (Gedan sungrab minyam gyunphel series, 1974)
Writings, chiefly on Buddhist philosophy and Lamaist ritual, of a Gelukpa polymath of Amdo.